Identifying and Integrating Relevant Educational/Instructional technology (E/IT) for Culturally and Linguistically Diverse (CLD) Students with Disabilities in Urban Environments - Brown, Monica R. (Journal of the American Academy of Special Education Professionals, 2013)
The aim of this manuscript is to address the significant void in the literature related to technology integration for culturally and linguistically diverse (CLD) students with disabilities living in urban communities. Given that the vast majority of CLD students attend school within urban districts, the focus of this article is to (a) identify and address the challenges students and educators encounter with technology integration in urban environments, (b) deconstruct the discrepancy between the need and the ability to implement AT and I/ET in urban school settings, and (c) identify and provide relevant resources and recommendations for educators working in urban school districts who have limited access to I/ET.